Optimization Of Temperature And Time For The Quality Of Probiotic Yogurt Using Custom Incubator - Deni Yannuarsita; Nugroho Dwi Prasojo; Moch Shandy Sasmito (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to determine the best temperature and time to incubate the yogurt making process by using a custom incubator as a fermentation tool for the quality of yogurt which includes the content of protein, fat, total acid, and lactic acid bacteria (LAB) Methodology: This study uses a Factorial Complete Random Design (RAL), the first factor is temperature (S1=36ºC, S2=39ºC, S3=42ºC) and the second factor is time (T1=8 hours, T2=12 hours, T3=16 hours, T4=20 hours) each treatment is repeated three times, the data obtained is statistically analyzed using Analysis of Variance (Anova). If there is a real difference, it is continued with Duncan's New Multiple Range Test (DNMRT) at the level of 5% and 1%. Results: The temperature difference had a real effect (P<0.05) on the levels of protein, fat and LAB while the time difference had a real effect (P<0.05) on protein, fat, total acid and LAB. The interaction of temperature and time treatment had a real effect (P<0.05) on the content of Protein, Fat, Total Solid and LAB. Findings: The use of 39ºC temperature and 16 hours was able to produce a protein content of 3.77%, a total acid level of 0.85%, and a number of lactic acid bacteria of 8.99 log cfu/ml. Novelty: This study provides information that the combination of high temperature use and short time can speed up the incubation process. Originality: This study explains the effect of temperature and time on the quality of yogurt. Conclusion: high temperature and short time with custom incubator can produce yogurt according to SNI. Document Type: Experimental Research Article